Riqueza de Tephritidae (Diptera) em associação com espécies vegetais no Campus I da Universidade de Passo Fundo - Lúz, Felipe da (2018)
The Tephritidae family is commonly known to be associated with fruit flies. 35% of the species from this family attack soft fruits and 40% develop in flowers of Asteraceae, the other species develop in flowers, leaves, branches or roots of other botanical families, being reported in the literature a species of the genus Tomoplagia found promoting gall in plants of the Vernoniae tribe. This study aimed to understand the fauna of Tephritidae present in Campus I of the University of Passo Fundo and its associations with hosts. A total of 64 plant species were collected from eight botanical families. It was possible to analyze a large diversity of Diptera of the Tephritidae family associated to capitula of Asteraceae,making new records occurrences for the state of Rio Grande do Sul, and to observe a new host for the species Tetreuaresta obscuriventris and Plaumanimmyia dolores. The species Tomoplagia rudolphi was found for the first time in the state causing stem galls in Vernonanthura tweediana (Vernoniae) which is also a new host for this species. In the observation of the fruit species present in the Campus, it was possible to find a massive infestation of Diptera of the genus Anastrepha whit a significant preference for plants of the family Myrtaceae. It was also observed Anastrepha fraterculusinfesting plants of the family Solanaceae, which is a novelty for the behavior of the species in the state of Rio Grande do Sul. The genus Anastrepha is one of the four genera considered of economic importance in Brazil, being the most polyphagous among them and responsible for the greater commercial losses in the national fruit growing. Another genus of economic importance is the genus Rhagoletis that was observed in this study infesting plants of the genus Solanum. Few studies in the state are developed with the purpose of knowing the incidence of individuals of this genus, which makes us understand the importance of this study to contribute to the knowledge of the dipteran entomofauna of the Tephritidae family in the northern region of the state of Rio Grande Sul.